2015
DOI: 10.1159/000377735
|View full text |Cite
|
Sign up to set email alerts
|

Utilisation of Blood Components in Trauma Surgery: A Single-Centre, Retrospective Analysis before and after the Implementation of an Educative PBM Initiative

Abstract: Background: The aim of our single-centre retrospective study presented here is to further analyse the utilisation of allogeneic blood components within a 5-year observation period (2009-2013) in trauma surgery (15,457 patients) under the measures of an educational patient blood management (PBM) initiative. Methods: After the implementation of the PBM initiative in January 2012, the Institute of Transfusion Medicine und Transplantation Immunology educates surgeons and nurses at the Department of Trauma Surgery … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 39 publications
0
5
0
Order By: Relevance
“…Patients undergoing cardiac surgery, such as CABG, have a high bleeding risk with some studies reporting over 50% requiring red cell transfusion in the general population 5 . The bleeding is multifactorial and the use of intravenous heparin with subsequent protamine reversal, to allow for the safe conduct of anastomoses and maintenance of graft patency, may be contributory 6 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Patients undergoing cardiac surgery, such as CABG, have a high bleeding risk with some studies reporting over 50% requiring red cell transfusion in the general population 5 . The bleeding is multifactorial and the use of intravenous heparin with subsequent protamine reversal, to allow for the safe conduct of anastomoses and maintenance of graft patency, may be contributory 6 .…”
Section: Introductionmentioning
confidence: 99%
“…Patients undergoing cardiac surgery, such as CABG, have a high bleeding risk with some studies reporting over 50% requiring red cell transfusion in the general population. 5 The bleeding is multifactorial and the use of intravenous heparin with subsequent protamine reversal, to allow for the safe conduct of anastomoses and maintenance of graft patency, may be contributory. 6 On thromboelastography (TEG), one study documents a prolongation of the TEG-R after protamine administration in a patient with severe haemophilia A, which corrected with a factor VIII (FVIII) bolus.…”
Section: Introductionmentioning
confidence: 99%
“…The result of that study indicated a better kidney outcome for the groups, in which the transfusion was circumscribed. [ 5 ] It is well known among the practitioners that blood transfusion is most of the time depending on clinical manifestation; however, using such protocols and algorithm would lead to a more accurate evaluation of patient's status and a better-individualized plan for each person.…”
Section: Discussionmentioning
confidence: 99%
“…Of note, using BCs in a good manner can result in a PC transfusion reduction. [ 5 ] The aim of the study is to investigate whether appropriate BC therapy can reduce blood transfusion and it would result in AKI decreasing.…”
Section: Introductionmentioning
confidence: 99%
“…By contrast, Geissler et al reported in 2015 in a subgroup analysis that patients with multiple trauma on average required 8-10 units of PRBCs, 17 units of fresh frozen plasma (FFP), and 3 units of platelets during their hospital stay [43].…”
Section: Theoretical Need For Blood Products In a Mass-casualty Terromentioning
confidence: 98%